Unusual Esophageal Foreign Body: A Table Fork. (24th March 2013) - Mevio, Emilio; Mevio, Niccolò
Abstract : The presence of an esophageal foreign body (EFB) is a medical emergency requiring urgent evaluation and treatment. Swallowing of foreign bodies is most common in children aged between 6 months and 6 years, in whom it usually occurs during games. In adults, foreign bodies tend to be ingested accidentally together with food. The authors report an unusual case of EFB (a table fork) in an adult and briefly report the clinical presentation and the therapeutic procedures adopted in this case and similar cases.